Maximum efficiency and parametric optimum selection of a concentrated solar spectrum splitting photovoltaic cell-thermoelectric generator system. (15th October 2018) - Yang, Zhimin; Li, Wangyang; Chen, Xiaohang; Su, Shanhe; Lin, Guoxing; Chen, Jincan
Highlights: A spectrum splitting photovoltaic-thermoelectric generator system is updated. Maximum efficiencies of the system are calculated for differently given parameters. The area ratio of the collector to the photovoltaic cell is optimized. Optimal values of some key parameters are determined. Advantages of the system are revealed, compared to the single photovoltaic cell. Abstract: An updated model of the solar spectrum splitting photovoltaic cell-thermoelectric generator system is used to derive the analytical expression of the systemic efficiency. The cutoff energy of the system, cell voltage, and dimensionless current of the thermoelectric generator are optimized. Particularly, the influences of the area ratio of the collector to photovoltaic cell on the performance of the spectrum splitting system are discussed in detail. The maximum efficiencies of the spectrum splitting system are calculated for given solar concentration factors. The results obtained are compared with those of the single photovoltaic cell with the same solar concentration factor. It is found that the maximum efficiency of the system can be further improved when the area ratio is optimized. The expressions of the upper and lower bounds of the optimized area ratio are derived. The spectrum splitting system can more efficiently harvest the full solar spectrum than the single photovoltaic cell, especially at low solar concentration factors. For example, when solar concentration factors are, respectively, equal to 30 and 100, the maximum efficiencies of the spectrum splitting system attain 39.5% and 40.2% and increase approximately 2.67% and 2.19%, compared to those of the single photovoltaic cell.